1998
DOI: 10.1164/ajrccm.157.3.9709042
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mild Sleep-disordered Breathing with CPAP Compared with Conservative Therapy

Abstract: The aim of this randomized controlled trial was to assess the effects of treatment with continuous positive airway pressure versus conservative therapy (CT) on well-being, mood, and functional status in subjects with mild sleep-disordered breathing (SDB). One hundred and eleven subjects, aged 25 to 65 yr, with a respiratory disturbance index (RDI) of 5 to 30 and without subjective pathologic sleepiness, were randomized to nasal CPAP or to CT. Ninety-seven subjects were followed-up after 8 wk. Treatment respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(144 citation statements)
references
References 23 publications
5
129
0
5
Order By: Relevance
“…These investigators reported that CPAP running time was 66% of the reported sleep-time in continuing users at 28 week follow-up. More recently, other workers observed that patients with mild to moderate degrees of OSA used CPAP for less than half of their total sleep-time [6]. In addition, sleep duration after CPAP initiation was significantly reduced in long sleepers [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These investigators reported that CPAP running time was 66% of the reported sleep-time in continuing users at 28 week follow-up. More recently, other workers observed that patients with mild to moderate degrees of OSA used CPAP for less than half of their total sleep-time [6]. In addition, sleep duration after CPAP initiation was significantly reduced in long sleepers [21].…”
Section: Discussionmentioning
confidence: 98%
“…It has also been suggested that compliance is better defined by CPAP use in relation to total subjective sleep-time. Using this approach, CPAP was used for 44% up to 68% of time subjects were estimated as being asleep [5,6]. Although good CPAP compliance is frequently defined as usage >5 h .…”
mentioning
confidence: 99%
“…Previous studies investigating the effects of CPAP on neuropsychological performance in SAS, were typically of short duration (weeks) and normally included only a small number of subjects [10±12, 14,15]. With these limitations in mind, the results of these previous studies consistently show that CPAP improves sleepiness, vigilance, mental flexibility, attention, mood, functional status, general health and energy/fatigue in patients with mild, moderate and severe SAS [10±12, 14,15,17]. The results of the present study at 3 months (figs.…”
Section: Discussionmentioning
confidence: 99%
“…8 The benefit of CPAP in treating the sleepiness associated with OSAHS has been well established. [50][51][52][53][54] The patient's perceived quality of life showed a significant increase after treatment. [51][52][53] Interestingly, the spouses of OSAHS patients also gained from CPAP therapy, as it eliminated the impairment of their own sleep due to the snoring and sleep disruption caused by bed partners.…”
Section: Positive Airway Pressure Therapy:-mentioning
confidence: 98%